Combined effects of drought and heat stress on morphology, physiology and yield of quinoa (Chenopodium quinoa) - SUBUDHI, ASHOK KUMAR; PRADHAN, ALIZA; SHARMA, D K; KUMAR, M; JANGID, K K; SHID, D; CHAVAN, S B; SINGH, A K; REDDY, K SAMMI (The Indian Journal of Agricultural Sciences, 2026)
Climate change threatens global crop production and food security, especially in marginal areas prone to drought, high temperatures, and resource limitations compounded by rapid population growth. In this context, quinoa (Chenopodium quinoa Willd.) is gaining attention as a climate-resilient crop due to its exceptional adaptability to harsh environments. Despite its tolerance, quinoa often encounters multiple abiotic stresses simultaneously primarily water scarcity and elevated temperatures which can significantly impair its physiological functions and yield. The study was carried out during the winter (rabi) seasons of 2022 and 2023 at the controlled environment facility (growth chamber) of ICAR-National Institute of Abiotic Stress Management, Baramati, Maharashtra to investigate the combined effects of drought and heat stress on quinoa. The experiment was laid out in a completely randomised design (CRD) with eight replications having four treatments, viz. Control [100% field capacity (FC)], 32/20°C (day/ night), drought (50% FC, 32/20°C); heat (100% FC, 36/24°C) and combined drought + heat (50% FC, 36/24°C). Quinoa variety used for the study was ‘Jaipur local’. The stresses were imposed at crop vegetative, flowering, and grain filling stages to evaluate their influence on overall growth, physiology and productivity. Findings indicated that the concurrent application of drought and heat stress had the most detrimental effect, surpassing the impact of each stress applied independently. Morphological parameters were most affected by stress imposed at vegetative stage while physio-chemical parameters were affected by stress imposed at flowering and grain filling stages. Drought + heat, heat and drought stress reduced quinoa seed yield by 82, 67 and 48%, respectively as compared to control (1106 kg/ha). These findings provide valuable insights for researchers and farmers, highlighting the need to optimize crop production techniques for quinoa in marginal environments.